Assessment of local carotid stiffness in seronegative and seropositive rheumatoid arthritis. (3rd September 2017) - Aslan, Abdullah Nabi; Şirin Özcan, Ayşe Nur; Erten, Şükran; Alsancak, Yakup; Durmaz, Tahir
Abstract: Objectives: Rheumatoid arthritis (RA) is a chronic, inflammatory disease associated with increased risk of cardiovascular (CV) disease. Arterial stiffness (AS) is an independent predictor of CV events. This study aimed to analyse local carotid AS parameters in seronegative and seropositive RA patients. Design: Of 347 consecutive RA patients, we selected specifically those who were free of established CV diseases and risk factors. As a result, 140 patients (126 women, 52.2 ± 10 years) and 140 healthy controls (122 women, 52.7 ± 8.0 years) were enrolled into this study. The common carotid AS was evaluated using radio frequency echo-tracking system to determine the local carotid pulse wave velocity (cPWV) and carotid intima-media thickness (cIMT). Based on rheumatoid factor (RF) and/or anti-citrullinated protein antibody (ACPA) positivity, RA patients were categorized into seronegative and seropositive subgroups. Results: Carotid PWV was determined to be significantly higher in all patients and subgroups than controls ( p < .001 for all). Although cIMT was similar between the patients, controls and seropositive subgroup, seronegative patients had significantly higher cIMT compared to controls ( p = .035) and seropositive group ( p = .010). Moreover, a significant positive correlation was found between cPWV and age ( r : 0.603, p < .001), ESR ( r : 0.297, p = .004), ACPA ( r : 0.346, p = .001) and cIMT ( r : 0.290, p = .005) in seropositive patients. Conclusions: RA per se is sufficient to cause arteriosclerosis in the absence of classical CV risk factors. However, arterial hypertrophy is only increased in seronegative patients but not in seropositive group.